La surveillance biologique de la fonction hépatique. - NEFOUSSI, Hafsa (My University, 2020)
The distressing nature of liver diseases, in particular viral hepatitis, and for the patient and his family on the one hand and on the other a major concern for the public authorities, taking into account the severity and evolution of the disease and its repercussions negative on society and the public treasury.. The aim of this thesis is to demonstrate the importance of early biological detection of liver diseases through periodic and regular analyses of liver function, also make the comparison between the paltry cost of the liver balance and the huge financial expense provided by the company to manage liver disease and its complications. Promoting preventive culture over costly curative culture must be a priority in our country’s future health care system.
Keywords: Liver; viral hepatitis; public treasure; early detection; financial expenditure; complications; prevention.